Optimization of Solid Organic Fertilizer of Dairy Cattle Feces and Layer Chicken on Growth of Kangkong (Ipomoea reptans Poir) - Anggraeni, Dita Arum; Dohong, Salundik; Karti, Panca Dewi Manu Hara (Universitas Halu Oleo, 2023)
This study analyzes the macronutrient levels produced from solid organic fertilizer made from dairy cows and laying hens and tests the effectiveness of fertilizer on land kangkong (Ipomoea reptans Poir) grown on latosol soil. The decomposition of feces into solid organic fertilizer was carried out using local microorganisms made from cattle rumen. Experiments were carried out using the repeated measures ANOVA method to observe the kinetics of pH and composting temperature from the first to the 30th day. The composition of 55% dairy cow feces and 45% laying hen feces in solid organic fertilizer can influence pH and temperature kinetics during the composting process. The first factor is the fertilizer composition of 100% dairy cow feces (S100), 85% dairy cow feces and 15% laying hen feces (S85A15), 70% dairy cow feces and laying hen feces (S70A30), 55% dairy cow feces and 45% laying hen feces (S55A45). The second factor is 5 and 10 tons/ha fertilizer dose. Using 100% dairy cow feces at a dose of 10 tons/ha affected the fresh biomass of land kangkong plants and significantly differed from other treatments (P < 0.05) based on a 5% BNJ follow-up test. It can be concluded that using dairy cow feces as much as 100% in the manufacture of solid organic fertilizer can increase the productivity of fresh biomass of land kangkong, which is highest at 30.22 g. Keywords: dairy cow feces, laying hens feces, Ipomoea reptans poir, local microorganisms, solid organic fertilizer